Air pollution, a rising environmental risk factor for cognition, neuroinflammation and neurodegeneration: The clinical impact on children and beyond - Calderón-Garcidueñas, L.; Leray, E.; Heydarpour, P.; Torres-Jardón, R.; Reis, J. (Revue neurologique, 2016)
Air pollution (indoors and outdoors) is a major issue in public health as epidemiological studies have highlighted its numerous detrimental health consequences (notably, respiratory and cardiovascular pathological conditions). Over the past 15years, air pollution has also been considered a potent environmental risk factor for neurological diseases and neuropathology. This review examines the impact of air pollution on children's brain development and the clinical, cognitive, brain structural and metabolic consequences. Long-term potential consequences for adults’ brains and the effects on multiple sclerosis (MS) are also discussed. One challenge is to assess the effects of lifetime exposures to outdoor and indoor environmental pollutants, including occupational exposures: how much, for how long and what type. Diffuse neuroinflammation, damage to the neurovascular unit, and the production of autoantibodies to neural and tight-junction proteins are worrisome findings in children chronically exposed to concentrations above the current standards for ozone and fine particulate matter (PM2.5), and may constitute significant risk factors for the development of Alzheimer's disease later in life. Finally, data supporting the role of air pollution as a risk factor for MS are reviewed, focusing on the effects of PM10 and nitrogen oxides.